FAKTOR-FAKTOR PENENTU KUALITAS JASA PERBANKAN DI SURABAYA (STUDI KOMPARASI PERSEPSI NASABAH DAN KARYAWAN) - Dhyka Bagus Permana (STIE Perbanas Surabaya, 2011)
The service quality is measured to evaluate the performance of bank services. In addition,SERVQUAL model is based on multi-item scale designed to measure the customers expectationsand perceptions. It also includes the gap that occurs, that is the gap between customersexpectation and the managements perception. These perceptions are also determined by thegender. This research aims to examine the factors which determine the quality of bankingservices for its customers and employees in Surabaya and examine different perceptions betweencustomers and bank employees. The sample consists of customers (adults and students)and bank employees in Surabaya. The data were collected by questionnaire, 80 questionnairesfrom general customers, 100 from students and 100 from bank employees have beencollected. It was found there are seven factors as the determinants of the quality of bankingservice perceived by customers and employees. From seven factors, there are differences inperceptions of service quality determinants between customers and employees. Based on customerperception, the speed and certainty of service time are the most important factor, whilebased on employees perception, courtesy and the employees competence are the most determinefactor